2020
DOI: 10.26740/jaj.v11n2.p110-121
|View full text |Cite
|
Sign up to set email alerts
|

Work Motivation Effect on State Civil Apparatus Performance during WFH with Discipline Variable

Abstract: Civil apparatus of the state should remain optimal in providing service to the community at the time of running work from home as a pandemic impact of Covid-19. Bureaucratic performance should also be maintained to ensure government programs can be directly perceived by the public. Governments are required to be able to apply flexible work patterns from two sides. That is flexible from the side of the work implementation, and flexible from the user side that in this case is the community.  Despite working from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Jamaludin, Azmir, Mohamad, and Zainal (2020) also agreed that work from home precludes the transmission of the virus as it precludes large presence of workers in the workplace. According to Bawono, Setyadi, and Hamid (2020) having a high work motivation is crucial in producing high performance workers even though they are working from home. Past studies have revealed that working from home increases job satisfaction (Baker, Avery, & Crawford, 2007;Dwidienawati, Tjahjana, Pradipto, & Gandasari, 2020;Kröll & Nüesch, 2019;MacRae & Sawatzky, 2020;Schall, 2019).…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Jamaludin, Azmir, Mohamad, and Zainal (2020) also agreed that work from home precludes the transmission of the virus as it precludes large presence of workers in the workplace. According to Bawono, Setyadi, and Hamid (2020) having a high work motivation is crucial in producing high performance workers even though they are working from home. Past studies have revealed that working from home increases job satisfaction (Baker, Avery, & Crawford, 2007;Dwidienawati, Tjahjana, Pradipto, & Gandasari, 2020;Kröll & Nüesch, 2019;MacRae & Sawatzky, 2020;Schall, 2019).…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Job performance is referred to as task proficiency, and it is assessed on the job by one's current manager [19]. The Concept of Action and Work states that The individual, the organizational climate, and the type of work all have a substantial impact on an organization's effectiveness [20].…”
Section: Job Performancementioning
confidence: 99%
“…Along with its development, all organizations, including government organizations, must be able to compete to deliver maximum service [1] [2]. Similarly, government officials as government servants must be able to provide the best service because this is one of the responsibilities of the government, which is tasked with carrying out the entire process of implementing development in various sectors of life from the central to the regional level [3].…”
Section: Introductionmentioning
confidence: 99%